Integration of Personnel Information Systems Between the Indonesian National Armed Forces Data and Information Processing Agency and the Indonesian National Armed Forces Personnel Administration Center in Supporting the Management of National Army Personnel Data - Polykrates; Didi Effendi; Ado Andhika Herlambang; Manahan Budiarto Pandjaitan (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The synergy between the Indonesian National Armed Forces Information and Data Processing Service and the Personnel Administration Center of the Indonesian National Armed Forces constitutes a crucial factor in supporting the effective and efficient management of personnel data across military branches. This study aims to analyze the forms of synergy between these two institutions in managing personnel data and to identify the challenges faced in realizing an integrated information system within the environment. This research employs a qualitative approach with a descriptive method through data collection techniques, including literature review, analysis of policy documents, and examination of personnel data management systems implemented within the National Army. The results indicate that the synergy between the Indonesian National Armed Forces Information and Data Processing Service and the Personnel Administration Center of the Indonesian National Armed Forces plays a strategic role in supporting the integration of personnel data management across the three military branches: the Indonesian Army, the Indonesian Navy, and the Indonesian Air Force. Indonesian National Armed Forces Information and Data Processing Service is responsible for providing and developing information system infrastructure as well as ensuring data security, while Personnel Administration Center of the Indonesian National Armed Forces is tasked with managing administrative processes and validating personnel data. The study also identifies several challenges in implementing this synergy, including differences in data management standards across branches, limited interoperability of information systems, and the need to enhance human resource competencies in the field of information technology. Therefore, it is necessary to strengthen institutional coordination, standardize data management systems, and leverage digital technologies such as Artificial Intelligence and the Internet of Things to support organizational digital transformation.